'Adrenal incidentalomas'; Rationalising assessment in the urology multi-disciplinary team meeting. (March 2019) - Siraj, Mamoon; Tolofari, Sotonye; Yow, Lina; Sinclair, Andrew; Javed, Saqib; Mukherjee, Rono; Bell, Richard; Lynch, Niall; Counsell, Andrew; Pollard, Alfred; Lewis, Philip; Adeyoju, Adebanji
The combination of an aging population and the continual technological advances in modern imaging techniques have contributed to the increased detection of asymptomatic incidental lesions. The definition of an adrenal 'incidentaloma' is an asymptomatic lesion (⩾1 cm) detected on imaging following a suspected alternative primary diagnosis. The majority of these adrenal incidentalomas, may be benign and non-functioning, however, a proportion of these lesions may be either malignant or 'hyperfunctioning' (hormone-producing). As such, these incidental and asymptomatic lesions can provide the urologist with a diagnostic dilemma. In this article we aim to review the current literature with reference to common clinical scenarios often encountered as part of the urology multi-disciplinary team meeting. The overall aim is to rationalise and standardise an approach to these often challenging scenarios.